PENGAMANAN FILE DOKUMEN DENGAN KOMBINASI ALGORITMA ELGAMAL DAN TEKNIK KOMPRESI ALGORITMA STOUT CODES - Szalfa Saadiatus Sakinah; Asep Id Hadiana; Fatan Kasyidi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The rapid advancement of technology brings both positive and negative impacts, one of the negative impacts is the risk of hacking important data and documents. Document security becomes very important to protect sensitive information from unauthorized access and unwanted modification. This research aims to secure document files by combining ElGamal cryptographic algorithm and Stout Codes compression technique. The ElGamal algorithm used for encryption, converting the original information into unintelligible codes, while Stout Codes is applied to reduce the size of the data to make it more efficient in storage and transmission. The results show that the combination of these two algorithms is able to scramble the contents of the document into ciphertext that is difficult to understand by unauthorized parties. Tests were conducted on 10 document files in .docx and .pdf formats, resulting in an average compression ratio of 382% and space saving of -282% for the encryption-compression process, and an average compression ratio of 659% and space saving of -559% for the compression-encryption process. In terms of entropy, the encryption-compression process shows a higher value of 6.59828, compared to the entropy value in the compression-encryption process of 3.214782. This indicates a better level of security in the encryption-compression process.